After TGN1412: Recent developments in cytokine release assays. (March 2013) - Stebbings, R.; Eastwood, D.; Poole, S.; Thorpe, R.
<x xml:space="preserve">Abstract</x> The failure of regulatory science to keep pace with and support the development of new biological medicines was very publically highlighted in March 2006 when the first-in-man Phase I clinical trial of the immunomodulatory CD28-specific monoclonal antibody (mAb) TGN1412 ended in disaster when all six volunteers suffered a life-threatening adverse reaction termed a 'Cytokine Storm'. The poor predictive value of standard pre-clinical safety tests and animal models applied to TGN1412 demonstrated the need for a new generation of immunotoxicity assays and animal models that are both sensitive and predictive of clinical outcome in man. The non-predictive result obtained from pre-clinical safety testing in cynomolgus macaques has now been attributed to a lack of CD28 expression on CD4+ effector memory T-cells that therefore cannot be stimulated by TGN1412. In contrast, high levels of CD28 are expressed on human CD4+ effector memory T-cells, the source of most TGN1412-stimulated pro-inflammatory cytokines. Standard in vitro safety tests with human cells were also non-predictive as they did not replicate in vivo presentation of TGN1412. It was subsequently shown that, if an immobilized therapeutic mAb-based assay or endothelial cell co-culture assay was used to evaluate TGN1412, then these would have predicted a pro-inflammatory response in man. New in vitro assays based on these approaches are now being applied to emerging therapeutics to hopefully prevent a repeat of the TGN1412 incident. It has emerged that the mechanism of pro-inflammatory cytokine release stimulated by TGN1412 is different to that of other therapeutic mAbs, such that standard pro-inflammatory markers such as TNFα and IL-8 are not discriminatory. Rather, IL-2 release and lymphoproliferation are optimal readouts of a TGN1412-like pro-inflammatory response.